FUNGSI KOMUNIKASI INTERNASIONAL BAGI ASEAN - CHINA DALAM ACFTA DITINJAU DARI PENDEKATAN KEKUATAN EKONOMI (ECONOMIC POWER ) - Sinta Julina (Jurnal Citra, 2022)
ABSTRACT The research background is that with the signing of the ASEAN - China Free Trade Area (ACFTA), ASEAN and China will establish international communication. There is an international communication function for ASEAN and China in the ACFTA. Therefore, researchers are interested in examining the Functions of International Communication for ASEAN-China in the ACFTA in terms of the International Communication Approach, namely the Economic Power Approach. The problem formulation is What are the Functions of International Communication for ASEAN-China in terms of the Economic Power Approach. The research objective is to examine what are the International Communication Functions for ASEAN and China in the ACFTA in terms of the Economic Power Approach. To describe the formulation of the problem, the researcher uses the Economic Power Approach in International Communication proposed by Hamid Mowlana. This type of research is descriptive. Data collection methods use document-based research or internet-based research. Data Analysis Method uses a qualitative data analysis method.The results of this study are the International Communication Function for ASEAN-China in the ACFTA Viewed from the Economic Power Approach, namely First, the International Communication Function for ASEAN is to convey the message that ASEAN is in an effort to fight for the achievement of its national interests, namely obtaining profits and economic progress. Second, the function of International Communication for China is to convey the message that as an industrial country, in an effort to achieve its national interests, it becomes a superior country in the world. Third, the function of International Communication for ASEAN and China is to convey messages of the same interests to create harmony, peace and enhance image, reputation and cooperation.Key words :International Communication Function, ASEAN, China, ACFTA, Economic Power Approach